Stress in Nurses During the COVID 19 Pandemic - Keršytė, Ieva; Mikaliūkštienė, Aldona; Fatkulina, Natalja (Slauga. Mokslas ir praktika, 2022)
The COVID-19 pandemic is the largest global health crisis in over a century. Research provides evidence that corona virus has a significant impact on the well-being of health professionals. Nurses face additional sources of increased stress when dealing with the new coronavirus. The psychological health of nurses during a COVID-19 pandemic is of great importance as it may affect their performance and reduce the quality of care provided. The overall prevalence of stress, anxiety, depression and sleep disturbance among nurses during the pandemic outbreak indicates that at least one third of nurses experienced stress, anxiety, depression and sleep disturbance. In carrying out their duties to stop the spread of virus, healthcare workers put their lives at risk due to the increased risk of exposure to the virus, the demanding nature of their workload, and irregular or long working hours. The aim of the study was to analyse the scientific literature on stress experienced by nurses during the COVID-19 pandemic. Methods – the systematic literature review of Web of Science, PubMed and Google Scholar databases for articles on nurses’ stress during the COVID-19 pandemic. The results showed that nurses experience higher levels of stress during the COVID-19 pandemic compared to normal working conditions and that stress has a negative impact on nurses’ professional and personal performance.